-40-8v=-5(1+3v)

Simple and best practice solution for -40-8v=-5(1+3v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -40-8v=-5(1+3v) equation:


Simplifying
-40 + -8v = -5(1 + 3v)
-40 + -8v = (1 * -5 + 3v * -5)
-40 + -8v = (-5 + -15v)

Solving
-40 + -8v = -5 + -15v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '15v' to each side of the equation.
-40 + -8v + 15v = -5 + -15v + 15v

Combine like terms: -8v + 15v = 7v
-40 + 7v = -5 + -15v + 15v

Combine like terms: -15v + 15v = 0
-40 + 7v = -5 + 0
-40 + 7v = -5

Add '40' to each side of the equation.
-40 + 40 + 7v = -5 + 40

Combine like terms: -40 + 40 = 0
0 + 7v = -5 + 40
7v = -5 + 40

Combine like terms: -5 + 40 = 35
7v = 35

Divide each side by '7'.
v = 5

Simplifying
v = 5

See similar equations:

| -7x-8y=-2 | | -39.6=12-0.4s | | 4x+9=-x+4 | | -17+16-x=16 | | 2y-x=y-5 | | 0.25+.05=6.10 | | 5b^2-22b-15=0 | | 18+8t=9(t-2) | | 3h-12=11h+4 | | 8(-9-2+3v-6v)= | | 2(4)-y=2 | | -6x-4(-7x-13)=58 | | 2(3)-y=2 | | y+2.6=6.9 | | 4x-22=54 | | -n-5(-6-7)=-119 | | 4x^2+20x+25=64 | | -9(1+6+6v)= | | 100=x+(x+2) | | 4h-4=8 | | 61.94+56.06-x-45=38 | | -3(-2+9v)= | | -16t^2+18t+10=0 | | -7(n-5)-6n=4n+1 | | 6(2x+3)=11x-3-6x | | 2x^2+10y=-7 | | 11b+3=25 | | t^2-16t+64= | | (2z+1)+9=(6z-9) | | 11=1-7x-3x | | 8t^2+9t+5=0 | | 0.26=-2.5(76-4) |

Equations solver categories